The politics of food security Asian and Middle Eastern strategies - Bazoobandi, Sara (Gerlach Press, 2014)
The international food system is increasingly at risk. Increasing demand, limited and diminishing resources and rising volatility are putting new pressures on the agriculture sector globally. One of the growing critical threats to global stability and security is the inadequacy of food resources. This threat, exacerbated by global population growth, is illustrated by shifts in consumption patterns toward protein-rich diets and the growth of multinational food retail, which bring about a greater reliance on food imports. This book compares the food security policies of selected countries in Asia and the Middle East, and reviews the outcomes of policy applications in a broader context. Themes discussed include: -Shifts in regional and international foreign policy, such as new alliances between countries with rich agricultural resources and wealthier importing states -Creation of food security policy competition across regions -Foreign investments and investment risks for farmland investments -Social implications, such as potential unrest -Environmental sustainability of food security programs, such as the depletion of water resources -Impact of food security programs on trade policies and fiscal policies, such as import taxes and subsidies.